Implementation of Spaced Repetition Technique Using Flashcards to Improve Arabic Vocabulary Retention - Nafi'ah, Laily Maghfiratun; Wijaya, Mualim (STUDI ARAB, 2025)
This study aims to evaluate the effectiveness of the spaced repetition technique integrated with flashcard media in improving Arabic vocabulary retention in students. Quantitative methods with a pre-experimental design of the One Group Pretest-Posttest type were used in this study. The subjects of the study were 22 female students of Madrasah Tsanawiyah Nurul Jadid class VII, who were selected through total sampling techniques. Data were collected through pretest and posttest tests, then analyzed using normality tests and paired sample t-tests with the help of SPSS. The results showed an increase in the average value from 60.7 (pretest) to 87.2 (posttest) with a significance value of p = 0.000 <0.05. These findings indicate that the use of the spaced repetition technique with the help of flashcard media is effective in significantly increasing Arabic vocabulary retention. The implication of this study is that the spaced repetition technique with flashcard media can be used as an alternative for learning Arabic vocabulary.